If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 3 + 5(y + 2) = 0 Reorder the terms: y + 3 + 5(2 + y) = 0 y + 3 + (2 * 5 + y * 5) = 0 y + 3 + (10 + 5y) = 0 Reorder the terms: 3 + 10 + y + 5y = 0 Combine like terms: 3 + 10 = 13 13 + y + 5y = 0 Combine like terms: y + 5y = 6y 13 + 6y = 0 Solving 13 + 6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 6y = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 6y = 0 + -13 6y = 0 + -13 Combine like terms: 0 + -13 = -13 6y = -13 Divide each side by '6'. y = -2.166666667 Simplifying y = -2.166666667
| 77+-1x=168+-10x | | 2x-4=-(5x-3) | | 9*w=81+18 | | 92+10x-32=180 | | 1/2x-27=22 | | (x^2+3x)dx+(4x^2+4y)dy=0 | | 84=4(8)(2)+2(2)x | | s13/4 | | 60+(8x+56)=180 | | 3x+24+2x-3=55-4x+29 | | y=x^2+10x-3 | | 6+-8=2(2+1) | | 4x-10=2x+25 | | y=x^2+10-3 | | 10+2x+16=90 | | y=.5(250)+300 | | y+2+5(y+6)= | | y=.5(200)+300 | | 113+(12x-53)=180 | | y=.5(150)+300 | | (6x^5-7y^3)(2x^6+y^8)= | | y+2+5(y+5)= | | 5n-1.3=1.5 | | y=.5(100)+300 | | Y=34+(x-2) | | y=.5(50)+300 | | y=.5(0)+300 | | -3=4m+12-m | | 4/3y0 | | 2.7=x/2.00-2x | | x+3x+15=59 | | (18w^15)(8v^6)= |